Mechanical Strain Causes Adaptive Change in Bronchial Fibroblasts Enhancing Profibrotic and Inflammatory Responses. - Wiparat Manuyakorn; David E Smart; Antonio Noto; Fabio Bucchieri; Hans Michael Haitchi; Stephen T Holgate; Peter H Howarth; Donna E Davies (PLoS ONE)
Asthma is characterized by periodic episodes of bronchoconstriction and reversible airway obstruction; these symptoms are attributable to a number of factors including increased mass and reactivity of bronchial smooth muscle and extracellular matrix (ECM) in asthmatic airways. Literature has suggested changes in cell responses and signaling can be elicited via modulation of mechanical stress acting upon them, potentially affecting the microenvironment of the cell. In this study, we hypothesized that mechanical strain directly affects the (myo)fibroblast phenotype in asthma. Therefore, we characterized responses of bronchial fibroblasts, from 6 normal and 11 asthmatic non-smoking volunteers, exposed to cyclical mechanical strain using flexible silastic membranes. Samples were analyzed for proteoglycans, α-smooth muscle actin (αSMA), collagens I and III, matrix metalloproteinase (MMP) 2 & 9 and interleukin-8 (IL-8) by qRT-PCR, Western blot, zymography and ELISA. Mechanical strain caused a decrease in αSMA mRNA but no change in either αSMA protein or proteoglycan expression. In contrast the inflammatory mediator IL-8, MMPs and interstitial collagens were increased at both the transcriptional and protein level. The results demonstrate an adaptive response of bronchial fibroblasts to mechanical strain, irrespective of donor. The adaptation involves cytoskeletal rearrangement, matrix remodelling and inflammatory cytokine release. These results suggest that mechanical strain could contribute to disease progression in asthma by promoting inflammation and remodelling responses.